(untitled) (Mugda Medical College Journal, 2026)
The global scenario of tuberculosis (TB) infection varies from one country to another; according to the World Health Organization (WHO), Bangladesh is one of the world’s 30 high TB burden countries and near about 73,000 people die annually due to tuberculosis. Several drugs are used in Category-1 and Category-2 regimen for TB treatment. Despite several side effects of these drugs, we have to use them invariably following the WHO guideline in our country. Although isoniazid and ethambutol have been associated with acute kidney injury (AKI), recent evidence showed that rifampin is the most common anti-TB drug responsible for AKI. Rifampicin toxicity may appear at both the initial administration and readministration. A 50-year old male pulmonary TB patient developed severe renal impairment after taking Category-1 anti-TB drugs. When severe renal impairment developed, anti-TB therapy was stopped and five sessions of hemodialysis were given. When renal function came back to normal, treatment was resumed with oral ethambutol and levofloxacin in full dose (excluding rifampicin). Later, oral isoniazid was added with low dose and increased dose was given based on monitoring of renal function. Even after adding injection streptomycin no deterioration of renal function was observed. We herein report this rare case and review of literature for academic interest and creating more awareness among the physicians. Mugda Med Coll J. 2026; 9(1): 92-94